MODERASI KEBIJAKAN DIVIDEN DALAM MEMPENGARUHI PROFITABILITAS DAN LIKUIDITAS DALAM MENINGKATKAN NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Hasanah, Ulfatun; Sari, Lita Permata; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The ultimate goal desired and achieved by a company is to obtain the maximum profit (profit) because to maintain the survival of a company. Profitability has many benefits, especially not only for company owners but also for parties outside the company. The purpose of this study was to determine the effect of dividend policy in moderating profitability and liquidity on firm value. The sampling technique used in this research is Purposive Sampling. The population in this study were LQ45 companies listed on the IDX in 2019-2022. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application, show that Profitability has a negative but insignificant effect on Firm Value, Liquidity has a negative but insignificant effect on Firm Value, Dividend policy positively but insignificantly moderates (weakens) the effect of Profitability on Firm Value, Dividend policy positively but insignificantly moderates (weakens) the effect of Liquidity on Firm Value.